An exploratory case study of the impact of expanding cost-effectiveness analysis for second-line nivolumab for patients with squamous non-small cell lung cancer in Canada: Does it make a difference?. Issue 6 (June 2018) - Shafrin, Jason; Skornicki, Michelle; Brauer, Michelle; Villeneuve, Julie; Lees, Michael; Hertel, Nadine; Penrod, John R.; Jansen, Jeroen
Highlights: In the payer analysis, nivolumab's NMB was −$1031 if QALYs were valued at $150, 000. Nivolumab had a positive NMB when value was measured from a societal perspective. Half of nivolumab's value was omitted under traditional payer analysis. Abstract: Introduction: Health technology appraisal agencies often rely on cost-effectiveness analyses to inform coverage decisions for new treatments. These assessments, however, frequently measure a treatment's value from the payer's perspective, and may not capture value generated from reduced caregiving costs, increased productivity, value based on patient risk preferences, option value or the insurance value to non-patients. Methods: To examine how using a broader societal perspective of treatment value affects cost-effectiveness estimates, this case study analyzed the net monetary benefit (NMB) of second-line nivolumab treatment of patients with squamous non-small cell lung cancer (NSCLC) in Canada. The comparator was treatment with docetaxel. NMB was measured from three perspectives: (i) traditional payer, (ii) traditional societal and (iii) broad societal. Results: Nivolumab was more effective (increased quality-adjusted life years by 0.66 versus docetaxel), but also increased costs by $100, 168 CAD. When valuing a quality-adjusted life year at $150, 000, the net monetary benefit from the payer perspective suggested that costs modestly exceed benefits (NMB: −$1031). Adopting a societal perspective, however, nivolumab's benefits outweighed its costs (NMB: +$6752 and +$91, 084 from the traditional and broad societal perspectives, respectively). Conclusion: Broadening cost-effectiveness analysis beyond the traditional payer perspective had a significant impact on the result and should be considered in order to capture all treatment benefits and costs of societal relevance.